Monitoramento de danos estruturais utilizando sensores de nanocompósitos - Takiuti, Breno Ebinuma [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
With the objective of structural health monitoring (SHM) in aerospace structures, several monitoring techniques have been studied. One of the most recent techniques is based on the use of continuous sensors, made of thin films of nanocomposites. The advantage of using such materials is the possibility to apply them on complex surfaces, covering larger areas and using few acquisition terminals. Moreover, by using the nanocomposites, it is possible to control its mechanical and electrical properties, making it possible to create a customized sensor for each case. The nanocomposite found most commonly in the literature for damage detection are the carbon nanotubes (CNT) composites, while the matrix depends on each case. This work proposes the use of alternative materials such as the ITO (Indium tin oxide) nanowires inserted at PMMA (Poly(methyl methacrylate)) to be used as coatings for the monitored structure. In order to verify the effectiveness of this sensor, several tests were proposed. These tests consists on monitoring the nanocomposite's behavior when affected by some kind of damage, in which can be simulated by a mass addition, excess of load or a crack. The principle for the damage detection is to measure the electrical resistance between two points at the film sensor and verify the variations caused by the damage to these measurements. In general, the obtained resistances varied from 1kΩ to 10kΩ, while with the damage appearance the measurements varied more than 30% at the path with the damage and at the paths nearby. Tests at the environmental chamber, with temperature and humidity control, showed that the sensor is sensitive to high temperatures and humidity levels. Regarding the sensibility to stress applied to the plate, the sensor showed changes at the resistances only when the plate started to deform plastically. The obtained results are promising and indicate that this method is effective for damage detection

Com o objetivo de assegurar a integridade estrutural de estruturas aeronáuticas, diversas técnicas de monitoramento da integridade estrutural têm sido estudadas. Uma das técnicas mais recentes é a utilização de sensores contínuos, constituídos de filmes delgados de nanocompósitos. A vantagem em se utilizar estes materiais é a possibilidade de se aplicar tais sensores em superfícies complexas, cobrindo uma grande área e utilizando poucos terminais de aquisição. Este tipo de material permite o controle das suas características mecânicas e elétricas, possibilitando a criação de um sensor customizado para cada situação. O nanocompósito mais encontrado na literatura para fins de detecção de falhas é o compósito de nanotubos de carbono (CNT), sendo que a matriz utilizada varia de acordo com cada caso. Este trabalho propõe a utilização de materiais alternativos como os nanofios de ITO (Indium tin oxide ou óxido de índio dopado com estanho) inseridos em matriz de PMMA (polimetil- metacrilato) para o revestimento da superfície a ser monitorada. Afim de verificar a efetividade destes sensores, diversos testes foram propostos. Estes testes consistem em monitorar o comportamento dos nancompósitos quando afetados por algum tipo de dano, os quais podem ser uma adição de massa, excesso de cargas tensoras ou uma trinca. Para isto, o intuito é medir as resistências elétricas entre dois pontos e verificar a influência do dano no valor medido. Em geral as resistências obtidas variaram entre 1kΩ e 10kΩ, sendo que com o aparecimento do dano, as medições apresentaram variações de mais de 30% tanto no caminho com o dano como nos caminhos em sua proximidade. Testes com o sensor em uma câmara ambiental, com controle de temperatura e umidade, mostraram que o sensor é sensível a altas temperatura e a altas umidades. Quanto à sensibilidade às tensões de tração aplicadas na placa, o sensor só mostrou alterações em sua...
Keywords: Monitoramento da integridade estrutural; Materiais inteligentes; Nanoestruturas; Localização de falhas (Engenharia); Structural health monitoring